Tiananmen 1989 : our shattered hopes - Zhang, Lun (Sociologist); Gombeaud, Adrien (Idea & Design Works, 2020)
Follow the story of China's infamous June Fourth Incident -- otherwise known as the Tiananmen Square Massacre -- from the first-hand account of a young sociology teacher who witnessed it all.